Guide to Qualitative Research in Parliaments Experiences and Practices - Berthet, Valentine; Gaweda, Barbara; Kantola, Johanna; Miller, Cherry; Ahrens, Petra; Elomäki, Anna (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
"This book is a must-read for so many people: it is an essential guide on how to do outstanding, transparent qualitative research; a critical reflection on the internal workings of the European Parliament; and a much-needed discussion of the role that gender, diversity and equality play in everyday (political) practices." ---Ariadna Ripoll Servent, Professor for Politics of the European Union, Salzburg University, Austria "Guide to Qualitative Research in Parliaments provides a concise, hands-on guide to qualitative parliamentary research, including all stages of the research process. Contributing fascinating insights from a research project, rich examples and practical guidance, this is a must-read for scholars interested in qualitative research and a useful tool for students." ---Josefina Erikson, Associate Professor in Political Science, Uppsala University, Sweden This open access book is a hands-on guide on doing qualitative research in parliaments, exploring achievements and drawbacks for all. From early-career scholars looking for an 'in' to start their research to senior academics interested in methodological details, the book offers a novel approach to discussing qualitative methodologies. It presents unique insights based on a large-scale qualitative study in the European Parliament using interview and ethnographic data. Comprehensive yet accessible, the book accounts the step-by-step process of qualitative research in parliaments, offering a reflexive and analytical perspective that moves beyond a textbook or theory-only format. Valentine Berthet is a postdoctoral researcher in the University of Helsinki, Centre for European Studies (CES). Barbara Gaweda is Senior Researcher in the University of Helsinki, Centre for European Studies (CES). Johanna Kantola is Professor of European Societies and their Politics in the University of Helsinki, Centre for European Studies (CES), Finland. Cherry Miller is a Lecturer in British and Comparative Politics at the University of Glasgow, Scotland, UK. Petra Ahrens is Academy Research Fellow at Tampere University, Finland. Anna Elomäki is Academy of Finland Research Fellow at Tampere University, Finland.